The Effect of Hostile Environment and Harassment on Employees' Turnover Intentions, Absenteeism and Employees' Performance: A Case Study of Tertiary Hospitals of Khyber Pakhtunkhwa, Pakistan - WAQAS AHMAD; HAJI MUHAMMAD ZUBAIR; SAYYAM (Journal of Business & Tourism, 2021)
The hostile environment and harassment in the workplace are a major problem in hospitals and have enormous negative consequences. The motive for this study is to look at the impacts of the hostile environment and, particularly, workplace harassment on performance, absenteeism and employee turnover intentions. The target population of the study was employees who worked in different KPK hospitals. The non-random snowball techniqueused to gather information from 255 respondents utilizing the questionnaire. The findings of this study show a clear picture about the relationships between study variables that the hostile environment and harassment in the workplace has a positive impact on employee turnover, absenteeism and negative impact on the performance of employees. Employees who work in hospitals need a safe and healthy environment for their commitment to duties and responsibilities. The numbers, facts and findings of this study prove that if hospitals do not provide a safe and healthy environment for employees, there must be negative consequences on the attitude or level of performance. As employees’ working in hospitals directly related to patients, if they are harassed and tense and environment is not supporting them that would leads to the general failure of hospitals.Hospital management must take serious action on such a hostile environment and whatever the circumstances, they must provide the safe and healthy environment for their employees as their basic requirement to work more positively and effectively.